Constraints on the Projected Tropical SST Response to Greenhouse Warming by the Observed Antarctic Sea Ice Concentration - Yu‐Fan Geng; Fengfei Song; Lu Dong; Fengyun Luo (Geophysical Research Letters)
Abstract The future tropical sea surface temperature (SST) changes profoundly impact global and regional climate. Under greenhouse warming, the reduction of Antarctic sea ice concentration (SIC) acts as an extratropical energy perturbation, exerting a substantial influence on the spatial distribution of tropical SST change. This study reveals a strong correlation between the current Antarctic SIC and tropical SST change, especially the interhemispheric asymmetry and El Niño‐like pattern under greenhouse warming among CMIP6 models. Considering the commonly underestimated Antarctic SIC in CMIP6 models, this study applies an emergent constraint on the projected tropical SST response to greenhouse warming using the observed Antarctic SIC. The interhemispheric asymmetry in projected tropical SST warming can be markedly diminished in the multi‐model ensemble mean, with a 30% reduction in the intermodel uncertainty. The spatial constraints on the projected tropical Pacific SST change produce a more pronounced and westward‐extended El Niño‐like warming pattern.